Research concerning the Indigenous Orang Asli and education: a review of problem representations. Issue 3 (3rd July 2022) - Renganathan, Sumathi
ABSTRACT: Research findings are necessary to inform, develop, and implement policies and strategies for positive outcome in education for Indigenous communities. This article analyses research publications concerning education for the Indigenous Orang Asli community in Malaysia. By analyzing the problems represented in the research papers, this article highlights how such problems have been shaped, understood, and addressed by researchers. The findings suggest that there are two main perceptions underpinning the various problems researched on Orang Asli and education. The first places Orang Asli themselves as the root of the problems. The second highlights the cultural mismatches between the minority Orang Asli and the majority culture, which are then construed as incompatible with the formal education available for Orang Asli students. These findings can assist future researchers on how to frame their research questions to better address issues related to Orang Asli and education, thus enabling better support for Indigenous education.